ANALISIS DIVIDEN SEBAGAI INDIKATOR KUALITAS LABA STUDI EMPIRIS PERUSAHAAN MANUFAKTUR SEKTOR KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aprina Nugrahesthy Sulistya Hapsari; Steven Sindu Santoso (Faculty of Economic and Business Universitas STIKUBANK, 2015)
The purpose of this research is to find out if the company which paying big dividend have better earnings quality than companies that paying small or do not pay dividend. The number of data samples 87, from manufacturing companies specified consumer goods in year of 2011-2013. The result show that the company which paying big dividend have better earnings quality and statistically significant. Keywords: Dividen, Kualitas Laba, Akrual